Top-Down Versus Bottom-Up Nanoengineering Routes to Design Advanced Oropharmacological Products - V. Singh, Ajay; K. Mehta, Krunal (Current Pharmaceutical Design, 2016)
Energy intensive and chemical routes predominately govern modern dental material fabrication involving complex physicochemical approaches. Current interest in dental material design is shifting towards biomineralization method and green chemistry synthesis to support oral tissue biocompatibility and oropharmacology. This review article describes the context of biophysical approaches based on development in nanoengineering to design advance nanomaterials for clinical dentistry. We particularly focus on approaches governing surface texture and hierarchical assembly emphasis based on micro-nanoscale tooth anatomy. Further, this article provides an overview about the merit of micro-nanoscale material design techniques exchanging the traditional dental material. In this context, top-down and bottom-up approaches involving biomimetic nanoengineering route, opportunities and challenges are discussed.
Keywords: odontoblast